2021
DOI: 10.1038/s41598-021-98310-3
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET biomarkers for prediction of survival in metastatic melanoma prior to anti-PD1 immunotherapy

Abstract: Our aim was to analyse whether biomarkers extracted from baseline 18F-FDG PET before anti-PD1 treatment contribute to prognostic survival information for early risk stratification in metastatic melanoma. Fifty-six patients, without prior systemic treatment, BRAF wild type, explored using 18F-FDG PET were included retrospectively. Our primary endpoint was overall survival (OS). Total metabolic tumoral volume (MTV) and forty-one IBSI compliant parameters were extracted from PET. Parameters associated with outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…What emerges from initial reports published so far on radiomics and AI in the context of immunotherapy setting is that no unique parameter or feature can be defined as superior ( Table 2 ). While features like “skewness” and “kurtosis”, well known from other types of treatment, might represent a marker of treatment failure during ICI in lung cancer [ 90 ], for other authors either Small Run Emphasis (SRE), multiparametric radiomics signature (mpRS), cytolytic activity score (CytAct), deeply learned score (DLS), or long zone emphasis (LZE) [ 89 , 91 , 92 , 93 , 94 ] can be as effective. What is missing in this clinical scenario is a solid ground truth, which can only be obtainable from preliminary reports validating imaging parameters with targets specifically relevant for immunotherapy, as in the case of PD-L1 expression.…”
Section: Next Generation Imaging For Immunotherapy In Cancermentioning
confidence: 99%
“…What emerges from initial reports published so far on radiomics and AI in the context of immunotherapy setting is that no unique parameter or feature can be defined as superior ( Table 2 ). While features like “skewness” and “kurtosis”, well known from other types of treatment, might represent a marker of treatment failure during ICI in lung cancer [ 90 ], for other authors either Small Run Emphasis (SRE), multiparametric radiomics signature (mpRS), cytolytic activity score (CytAct), deeply learned score (DLS), or long zone emphasis (LZE) [ 89 , 91 , 92 , 93 , 94 ] can be as effective. What is missing in this clinical scenario is a solid ground truth, which can only be obtainable from preliminary reports validating imaging parameters with targets specifically relevant for immunotherapy, as in the case of PD-L1 expression.…”
Section: Next Generation Imaging For Immunotherapy In Cancermentioning
confidence: 99%
“…The choice of the best radiomics parameters from the pretherapeutic 18F-FDG-PET to predict the outcome is still a matter of debate as results from previous studies are heterogeneous. One study reporting on SUVmax found SUVmean and tumor heterogeneity index were not correlated with OS or PFS in a heterogeneous cohort of 55 melanoma patients before anti-PD1 treatment [ 9 ]; however, other studies showed significant correlations between conventional or second order 18F-FDG PET parameters and melanoma patients’ outcomes after immunotherapy [ 8 , 10 , 29 ]. Authors showed conventional parameters, such as SUV max, SUVpeak, TLG and MTV, were associated with OS [ 8 , 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study reporting on SUVmax found SUVmean and tumor heterogeneity index were not correlated with OS or PFS in a heterogeneous cohort of 55 melanoma patients before anti-PD1 treatment [ 9 ]; however, other studies showed significant correlations between conventional or second order 18F-FDG PET parameters and melanoma patients’ outcomes after immunotherapy [ 8 , 10 , 29 ]. Authors showed conventional parameters, such as SUV max, SUVpeak, TLG and MTV, were associated with OS [ 8 , 10 , 29 ]. Second order features, such as tumor heterogeneity index, as well as long-zone emphasis from the GLZLM matrix were associated with OS [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations